Enhanced Ordering of Block Copolymer Thin Films upon Addition of Magnetic Nanoparticles - Konefał, Magdalena; Černoch, Peter; Patsula, Vitalii; Pavlova, Ewa; Dybal, Jiří; Załęski, Karol; Zhigunov, Alexander (ACS applied materials & interfaces, 2021)
The influence of magnetite nanoparticles coated with poly(acrylic acid) (Fe3O4@PAA NPs) on the organization of block copolymer thin films via a self-assembly process was investigated. Polystyrene-b-poly(4-vinylpyridine) films were obtained by the dip-coating method and thoroughly examined by X-ray reflectivity, transmission electron microscopy, atomic force microscopy, and grazing incidence small-angle scattering. Magnetic properties of the films were probed via superconducting quantum interference device (SQUID) magnetometry. It was demonstrated that due to the hydrogen bonding between P4VP and PAA, the Fe3O4@PAA NPs segregate selectively inside P4VP domains, enhancing the microphase separation process. This in turn, together with employing carefully optimized dip-coating parameters, results in the formation of hybrid thin films with highly ordered nanostructures. The addition of Fe3O4@PAA nanoparticles does not change the average interdomain spacing in the film lateral nanostructure. Moreover, it was shown that the nanoparticles can easily be removed to obtain well-ordered nanoporous templates.
Keywords: thin films; self-assembly; magnetite nanoparticles; block copolymer